An expert system for financial ratio analysis. (4th May 2006) - Moynihan, Gary P.; Jain, Vineet; McLeod, Robert W.; Fonseca, Daniel J.
Financial analysis interprets a company's past and present financial health and predicts its future condition. Although company financial statements contain a wealth of information to support this analysis, their interpretation may be complicated. Experts in this field are limited. This research focuses on automating the current practice of financial ratio analysis to identify the various features that need to be incorporated into the system. This involves calculating the ratios, establishing the relationships between the ratios, determining the technique for accurately forecasting the financial statements and/;or ratios, developing heuristics for analysing the ratios and providing a system for recommendations. A prototype expert system was then developed. The system is capable of performing five types of analysis: liquidity, leverage, turnover, profitability, and past performance. The output of the system is a list of conclusions and recommendations based on these analyses.